A Comparative study of some Immunological and Molecular Techniques to Detect Cytomegalovirus in patients with Kidney Failure in Diyala Governort - Mahmood, Shahad Shaker; Farhan, Abbas Abod; Saleh, Mohmmed Abdul Daim (Diyala Journal of Medicine, 2018)
Background: Kidney failure can be defined as the total failure of toxins and waste from filtration the blood. This disease is characterized by reduced glomerular filtration rate (GFR) to about 20-50% , resulting in the failure to regulate the amount of fluid in the body and it is divided into two types acute and chronic renal failure .The immunity of patients with haemodialysis becomes weak and this cause viral infections such as Cytomegalovirus human cells. Objective: To determine the relationship between kidney failure and Cytomegalovirus human cells and compare the molecular and immunological techniques in diagnose this virus. Patients and Methods: Seventy blood sample were collected from patients with kidney failure after diagnosis by specialists in the Ibn Sina Centre for dialysis and 20 individuals as acontrol. The IgG and IgM were detected by ELISA , in addition the diagnose of virus by cassette and compare the results of CMV diagnosis(by ELISA technique) with molecular technique (PCR) results. Results: ELISA results showed that the incidence of CMV IgG was 25 patients (35.7%) while IgM was in 5 patient (7.1%). The incidence of IgG in males was (56%). In females was (44%). while the result of IgM in male was (100%) and In females (5) The results of cassette showed CMV virus was seropositivity (21.4%) for males and females with very high difference observed between the two groups of study and more differences were observed between test results and sex between test results and age groups, and showed a positive PCR test results of interaction (66.6%) and (20) of (30) sample tested after ELISA techniques to detect IgG and IgM in comparison among three techniques used by PCR technique the best technique were IgG and IgM ELISA test results and test cassette and technique PCR molecular are 21.4% and 7.1% and 35.7% and 66.6%. Conclusion: The results showed that Cytomegalovirus has relationship with chronic and acute renal failure and can affect the patient's immune status. our results can provide an advanced diagnosis of viral infections among patients in hospitals in Iraq.